PEDAGOGICAL ANALYSIS OF HUMAN NATURE AND EDUCATION ANALISIS PENDAGOGIK TENTANG HAKIKAT MANUSIA DAN PENDIDIKAN - Atika Okta Rina; Arief Kuswidyanarko; Henni Riyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Humans are beings who possess the capacity to grow and develop through educational processes. In pedagogical studies, humans are not merely viewed as individuals with intellectual abilities, but also as social, moral, and spiritual beings who require guidance to optimize their potential. This article aims to examine the nature of human beings from a pedagogical perspective and its relationship to education. The method applied in this study is a literature review by analyzing educational theories and expert perspectives regarding humans as subjects of education. The findings indicate that education plays a significant role in shaping character, improving intellectual abilities, and instilling social as well as moral values. Furthermore, education serves as a means of helping individuals achieve maturity and adapt to social and technological changes. Therefore, understanding the nature of human beings becomes an essential foundation in the implementation of education so that learning processes can be carried out effectively and in accordance with the needs of learners.